2021
DOI: 10.3390/ijerph18020631
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale) Attenuates Obesity and Adipose Tissue Remodeling in High-Fat Diet-Fed C57BL/6 Mice

Abstract: Obesity is characterized by excessive fat accumulation in adipose tissue, which is an active endocrine organ regulating energy metabolism. Ginger (Zingiber officinale) is known to have antioxidant, anti-inflammatory, and antiobesity effects, but the role of ginger in modulating adipocyte metabolism is largely unknown. In this study, we hypothesized that ginger supplementation inhibits high-fat (HF)-diet-mediated obesity. C57BL/6 male mice were randomly assigned to three diets for 7 weeks: low fat (LF, 16% kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
5
22
0
Order By: Relevance
“…Diet supplementations with these spices could therefore ameliorate hyperglycemia and its accompanying consequences. The improved insulin sensitivity in the group fed ginger supplemented diet could be through up-regulation of FGF-21 as reported by Seok et al (2021). In addition to increasing energy expenditure and fat utilization, FGF21 is reported to prevent development of metabolic derangement by normalizing glucose and lipid homeostasis (Wing and Po, 2016).…”
Section: The Inducement Of Metabolic Syndrome In Ratsmentioning
confidence: 79%
See 1 more Smart Citation
“…Diet supplementations with these spices could therefore ameliorate hyperglycemia and its accompanying consequences. The improved insulin sensitivity in the group fed ginger supplemented diet could be through up-regulation of FGF-21 as reported by Seok et al (2021). In addition to increasing energy expenditure and fat utilization, FGF21 is reported to prevent development of metabolic derangement by normalizing glucose and lipid homeostasis (Wing and Po, 2016).…”
Section: The Inducement Of Metabolic Syndrome In Ratsmentioning
confidence: 79%
“…It follows from the finding that supplementation of the diet (2%) with any of ginger, garlic, turmeric and black pepper could retard/reverse the progression of obesity in diet-induced obese rats (Table 4) which could be due to increase in thermogenesis, energy expenditure and lipolysis coupled with inhibition of the intestinal absorption of dietary fat; conditions that could have been mediated by some bioactive compounds contained in the spices. Seok et al (2021) reported that ginger intake caused upregulation of fibroblast growth factor 21 (FGF21), acyl-CoA oxidase 1 (ACOX1), and carnitine palmitoyltransferase 1 (CPT1) all of which increase fatty-acid utilization and consequently cause decrease in weight. Previously, Sayed et al (2020) and Wang et al (2020) had demonstrated antiobesity properties of ginger which resulted into decrease in body weight and fat mass in models of animal.…”
Section: The Inducement Of Metabolic Syndrome In Ratsmentioning
confidence: 99%
“…When full‐text articles were assessed for eligibility criteria, a total of 75 studies were excluded. Finally, 20 eligible studies were identified, of which 17 in‐vivo experiments were included in the quantitative analysis/meta‐analysis (Bin‐Meferij, Shati, Eid, & El‐Kott, 2017; Chang, Liou, Tzeng, & Liu, 2014; Faran et al, 2019; H. Gao et al, 2012; Heeba & Abd‐Elghany, 2010; Kandeil, Hashem, Mahmoud, Hetta, & Tohamy, 2019; Lai et al, 2016; Leal et al, 2019; Lee, Ahn, Jang, Ha, & Jung, 2016; Liu, Huo, Zhang, & Zhang, 2003; Nammi et al, 2010; Nwozo, Osunmadewa, & Oyinloye, 2014; Sakr, Mahran, & Lamfon, 2011; Sharma & Singh, 2012; Shirpoor et al, 2018; Tzeng, Liou, Chang, & Liu, 2013; Seo, Fang, & Kang, 2021). 3 clinical trials were included in the qualitative analysis (Nayebi Far & Ghasemi, 2021; Rafie, Hosseini, Hajiani, Saki Malehi, & Mard, 2020; Rahimlou, Yari, Hekmatdoost, Alavian, & Keshavarz, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…;Nwozo, Osunmadewa, & Oyinloye, 2014;Sakr, Mahran, & Lamfon, 2011;Sharma & Singh, 2012;Shirpoor et al, 2018;Tzeng, Liou, Chang, & Liu, 2013;Seo, Fang, & Kang, 2021).3 clinical trials were included in the qualitative analysis (Nayebi Far & Ghasemi, 2021; Rafie, Hosseini, Hajiani, Saki Malehi, & Mard, 2020; Rahimlou, Yari, Hekmatdoost, Alavian, & Keshavarz, 2016). F I G U R E 1 Flow diagram of the literature search regarding the effect of ginger on fatty liver T A B L E 1 Characteristics of the included studies…”
mentioning
confidence: 99%
“…In another study, consumption of a high-fat diet supplemented with ginger powder (5%) caused improvements in body weight and gain, hepatic lipid levels, hyperglycemia, hypercholesterolemia, and lipogenic levels in C57BL/6 mice. Also, ginger enhanced levels of the fatty-acid oxidation gene, carnitine palmitoyltransferase 1 (CPT1), and downregulated the adipocyte inflammatory gene expression (Seo et al, 2021).…”
Section: Anti-obesity Potentialmentioning
confidence: 99%